Pengembangan Multimedia Interaktif untuk Diklat Tenaga Prawatan Listrik Aliran atas di BPTP Sofyan Hadi - Ragil Prasetyo Prasetyo (Jurnal Pembelajaran Inovatif, 2021)
This research aims to produce a product in the form of interactive multimedia that will be used as one of the supporting media of learning for the training of railway infrastructure maintenance personnel namely upper flow electricity in Sofyan Hadi Railway Engineering Training Center. In this development research, the development model used refers to the R&D (Research and Development) method by thiagarajan developed 4D development models that have stages consisting of: Define, Design, Develop, and Disseminate. Products developed from this study have gone through formative evaluation stages including Expert Review, One to One, and large-scale trials.The results of the Expert Review from learning media experts get a score of 3.80 (Excellent).The material expert gets a value of 3.70 (Excellent). One to One trial results get 3.60 (Excellent) results. Large-scale trial results get 3.60 (Excellent) results. Based on these results, it can be concluded that the Interactive Multimedia product for the Overhead Catenary Engineering Training is expressed very well.